The Potential Pests Of Corn Armyworm (Spodoptera litura) In The Food Estate Indonesia-Timor Leste Border Area: Indonesia - Hadisugelar, Danar (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2025)
Corn (Zea mays) is a staple food after wheat and is a source of food that can be processed into various product. The distribution of insects on corn can be distinguished by their roles such as herbivores, predators, parasitoids and pollinators. Armyworm (Spodoptera litura) is a pest that attacks corn plants and spreads to various countries. The results of research showed that armyworm attacks on maize between plots in the food estate area of ​​the RI-Timor Leste border area varied. Plot I had the highest damage with the percentage of attacks 66.94% and a damage intensity 33.47% belong to slightly heavy damage and Plot V had damaged with percentage of attack 43.89% and the intensity of damage reached 22.08% belong to slightly heavy damage category. Plots II and III had the lowest attack with attack percentage of 12.50% and a damage intensity 6.25% with a light damage category. The armyworm is a polyphagous pest that has a variety of host plants such as sorghum, carrots, mustard greens, spinach and others. Armyworm is pest that can be minor to major status